Variation of selected morphological characters of the cave mite Oribella cavatica Kunst, 1962 (Acari, Oribatida) - Żbikowska-Zdun, Krystyna; Piksa, Krzysztof; Smaczyńska, Anna (Biological Letters, 2010)
Two populations of Oribella cavatica were examined. The mites were isolated from bat guano collected in February 2006 in Zbójecka Cave in Mount Łopień and in the cave Czarci Dół, which are situated in the Beskid Wyspowy Mountains, within the Flysch Carpathians in southern Poland. Coefficients of variation of body length and width, lamella length, and sensillus length of this species under stenotopic conditions were compared with those of two eurytopic species. The stable variation of sensillus length of O. cavatica, like differences in the variation of Heminothrus peltifer in various soil habitats, may have bioindicative significance.